The environmental of New Mexico City International Airport, in Texcoco, State of Mexico - Moreno Sánchez, Enrique (2017)
The environmental dimension is linked to the construction of the New Mexico City International Airport, now in the municipality of Texcoco, as part of the State of Mexico. This airport is no longer located in Mexico City, which takes on another meaning in terms of public administration and governance. Environmental is expected to be a process linked to the socio-territorial configuration, and present modification in the first instance at the local level, which will be observable in the course of the building of the airport project. This paper presents research results with data from surveys conducted, fieldwork, data analysis, which allows us to infer the environmental trend in the municipality of Texcoco with the installation of the new international airport as well as the effect on the area of influence more immediate. The significance of this dimension and the opinion of the people can know the possible impact of the largest international airport in Latin America, and according to official version, of the three largest in the world.